An integrated transmission and distribution test system for evaluation of transactive energy designs. (15th April 2019) - Nguyen, Hieu Trung; Battula, Swathi; Takkala, Rohit Reddy; Wang, Zhaoyu; Tesfatsion, Leigh
Highlights: Evaluation of electric power system designs requires comprehensive test platforms. An open-source test platform is developed that permits this evaluation. The platform models integrated transmission and distribution system operations. The platform permits dynamic testing of bid-based transactive energy designs. Test cases demonstrate the capabilities of the platform. Abstract: This study presents an open-source software platform specifically tailored to permit careful dynamic performance evaluation of transactive energy designs for end-to-end electric power systems. The platform models a centrally-managed wholesale power market operating over a transmission grid linked to one or more distribution systems, where each distribution system consists of a collection of grid-edge resources operating over a distribution grid. Test case findings are presented to illustrate the capabilities of the platform. The test cases implement a transmission system linked to a distribution system populated by households that have smart price-responsive appliances as well as conventional loads. Transactions at the distribution level are conducted in accordance with a well-known bid-based transactive energy design known as the PowerMatcher.